Mid-term survival of patients with chronic kidney disease after extracorporeal membrane oxygenation. (2nd October 2020) - Lu, Yueh-An; Chen, Shao-Wei; Lee, Cheng-Chia; Wu, Victor Chien-Chia; Fan, Pei-Chun; Kuo, George; Chen, Jia-Jin; Chu, Po-Hsien; Chang, Shang-Hung; Chang, Chih-Hsiang
Abstract: OBJECTIVES: Chronic kidney disease (CKD) impairs the elimination of fluids, electrolytes and metabolic wastes, which can affect the outcomes of extracorporeal membrane oxygenation (ECMO) treatment. This study aimed to elucidate the impact of CKD on in-hospital mortality and mid-term survival of adult patients who received ECMO treatment. METHODS: Patients who received first-time ECMO treatment between 1 January 2003 and 31 December 2013 were included. Those with CKD were identified and matched to patients without CKD using a 1:2 ratio and were followed for 3 years. The study outcomes included in-hospital outcomes and the 3-year mortality rate. A subgroup analysis was conducted by comparing the dialytic patients with the non-dialytic CKD patients. RESULTS: The study comprised 1008 CKD patients and 2016 non-CKD patients after propensity score matching. The CKD patients had higher in-hospital mortality rates [69.5% vs 62.2%; adjusted odds ratio 1.41; 95% confidence interval (CI) 1.15–1.72] than the non-CKD patients. The 3-year mortality rate was 80.4% in the CKD group and 68% in the non-CKD group (adjusted hazard ratio 1.17; 95% CI 1.06–1.28). The subgroup analysis showed that the 3-year mortality rates were 84.5% and 78.4% in the dialytic and non-dialytic patients, respectively. No difference in the 3-year mortality rate was noted between the 2 CKD subgroups ( P  = 0.111). CONCLUSIONS: CKD was associated with increased risks of in-hospital and mid-term mortalities in patients who received ECMO treatment. Furthermore, no difference in survival was observed between the patients with end-stage renal disease and non-dialytic CKD patients. Abstract : Chronic kidney disease (CKD) has become a world-wild healthcare concern with a high prevalence rate, ranging from 3.1% to 15% in adults across European and North America [1, 2].